Unraveling the mechanisms and evolution of a two-domain module in IQGAP proteins for controlling eukaryotic cytokinesis - Kangji Wang; Hiroki Okada; Carsten Wloka; Erfei Bi (Cell Reports, 2023)
Summary: The IQGAP family of proteins plays a crucial role in cytokinesis across diverse organisms, but the underlying mechanisms are not fully understood. In this study, we demonstrate that IQGAPs in budding yeast, fission yeast, and human cells use a two-domain module to regulate their localization as well as the assembly and disassembly of the actomyosin ring during cytokinesis. Strikingly, the calponin homology domains (CHDs) in these IQGAPs bind to distinct cellular F-actin structures with varying specificity, whereas the non-conserved domains immediately downstream of the CHDs in these IQGAPs all target the division site, but differ in timing, localization strength, and binding partners. We also demonstrate that human IQGAP3 acts in parallel to septins and myosin-IIs to mediate the role of anillin in cytokinesis. Collectively, our findings highlight the two-domain mechanism by which IQGAPs regulate cytokinesis in distantly related organisms as well as their evolutionary conservation and divergence.